THE STUDY OF TOURISM AS AN APPLIED FIELD OF ANTHROPOLOGY - Dr Ullhas Dadhakar (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The ultimate goal of scientific inquiry is to enhance human lives through the implementation of research findings. This use of an anthropological notion has been done before. The findings of anthropology have been successfully applied to several sectors.Therefore, tourism has the potential to solve a variety of theoretical and practical anthropological problems. Tourism research conducted by anthropologists tends to focus on either the reasons that drive tourism or the knock-on effects of the sector. Therefore, although the study of tourists from an anthropological perspective is not exactly cutting-edge, there is still plenty to discover in this field.Tourist anthropology demonstrates that anthropology may be used as a lens for studying the dynamics of the tourism sector.